Architectural acoustic design: Observation of use cases including audio-only and multimodal auralizations. Issue 1 (March 2022) - Thery, David; Poirier-Quinot, David; Jouan, Sebastien; Katz, Brian FG; Boccara, Vincent
Auralization technology has reached a satisfactory level of ecological validity, enabling its use in architectural acoustic design. Only recently have the actual uses of auralization in the consulting community been explored, resulting in the identification of a variety of uses, including (1) to present to clients, (2) to test design ideas, (3) as a verification tool, (4) as a verification tool, (5) as a marketing tool, and (6) to improve internal company discussions. Taking advantage of methodologies from ergonomics research, the present study investigates effective uses through the observation of a collaboration project between an acoustic research team and an acoustic consultant, as a case study. Two spaces have been auralized in the context of the conception of a new skyscraper during the design phase of the project. The two spaces faced different problematics: an Atrium for which three different acoustic treatment options were suggested and experienced through multi-modal auralizations and audio-only auralizations of an Auditorium where an intrusive noise was to be acoustically treated. The ergonomic observation and analysis of this project revealed key impediments to the integration of auralization in common acoustic design practices.